2000
DOI: 10.3758/bf03200826
|View full text |Cite
|
Sign up to set email alerts
|

Efficient coding of eyewitness narratives: A comparison of syntactic unit and word count procedures

Abstract: Researchers rely on two types of coding systems to evaluate eyewitness narratives. Features-ofevents checklists offer coding simplicity but are impractical when target events are complex. Vnits-ofinformation (VOl) systems score all information reported, regardless of event complexity,but are difficult to implement. To test whether simpler systems would alter conclusions about memory performance, transcripts from children (3-8 years of age) who participated in an eyewitness study, originally coded using a VOl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The children's responses were coded with a modified word count procedure. This procedure correlates highly (r > .90) with the more commonly used units of information procedure (Dickinson & Poole, 2000).…”
Section: Data Codingmentioning
confidence: 79%
“…The children's responses were coded with a modified word count procedure. This procedure correlates highly (r > .90) with the more commonly used units of information procedure (Dickinson & Poole, 2000).…”
Section: Data Codingmentioning
confidence: 79%
“…Each memory description was then subjected to a word count, using Microsoft Word for Windows. Research in our laboratory has shown that word count is highly correlated with the number of clauses that a memory description contains, and Dickinson and Poole (2000) demonstrated that word count is highly correlated with the number of syntactic units that a memory description contains.…”
Section: Codingmentioning
confidence: 96%
“…Word count is an accepted tool in evaluating eyewitness narratives (Dickinson & Poole, 2000). As 25 of the interviews contained interpreters, some words came from the interpreters rather than the actual children.…”
Section: Words Spokenmentioning
confidence: 99%